Single vs. Combined Therapeutic Approaches in Rats With Chronic Spinal Cord Injury - Buzoianu-Anguiano, Vinnitsa; Rivera-Osorio, Jared; Orozco-Suárez, Sandra; Vega-García, Angélica; García-Vences, Elisa; Sánchez-Torres, Stephanie; Jiménez-Estrada, Ismael; Guizar-Sahagún, Gabriel; Mondragon-Caso, Jose; Fernández-Valverde, Francisca; Madrazo, Ignacio; Grijalva, Israel (Frontiers in Neurology, 2020)
Regenerative capability of the central nervous system is limited after traumatic spinal cord injury (SCI) due to intrinsic and extrinsic factors which inhibit spinal cord regeneration, resulting in deficient functional recovery. It has been shown that strategies such as pre-degenerated peripheral nerve (PPN) grafts, the use of bone marrow stromal cells (BMSCs) or exogenous molecules such as chondroitinase ABC (ChABC), promote axonal growth and remyelination resulting in an improvement of locomotor function. These treatments have been primarily assessed in acute injury models. The aim of the present study is to evaluate the ability of several single and combined treatments in order to modify the course of chronic complete SCI in rats. A complete cord transection was performed at T9 level. One month later, animals were divided into 5 groups: original injury only (control group), and original injury plus spinal cord re-transection to create a gap to accommodate BMSCs, PPN, PPN+BMSCs, and PPN+BMSCs+ChABC. In comparison to control and single-treatment groups (PPN and BMSCs), combined treatment groups (PPN+BMSCs, and PPN+BMSCs+ChABC) showed a significative axonal regrowth as revealed by an increase in GAP-43 and MAP-1B expression in axonal fibers, which correlated with the improvement in locomotor function. In conclusion, combined therapies tested here improve locomotor function by enhancing axonal regeneration in rats with chronic SCI. Further studies are warranted to refine this promising line of research for clinical purposes.